Síntese de híbridos moleculares contendo os núcleos morfolínico, 1,4-naftoquinônico, 7-cloroquinolínico e 1,3,5-triazínico com atividade inibidora de corrosão no aço AISI 316 em meio de água de produção simulada - Westphal, Regina (2019)
Corrosion is a recurring and troubling problem in many sectors of industry and society. The petroleum and petrochemical industries are the most affected by the phenomenon of corrosion, which is present throughout the production chain, causing operational delay, increased production costs, oil contamination and other serious damages to the environment and health or even to the life of employees. This is due to the presence of corrosive substances, such as Cl-, H2S, CO2 and O2, dissolved in the production water and oil. One way to mitigate the problems caused by corrosion is by injecting chemical inhibitors into the production line. The organic inhibitors (focus of this work) are substances that adsorb chemically to the surface of the steel, coordinating to the metal and, thus, forming a protective film. Therefore, it is interesting that these inhibitors have in their structures strongly polar insaturations and / or clusters such as nitrogen, sulfur or oxygen atoms, which have pairs of electrons available to be donated to metals. In this sense, the molecular hybrids 70, 71 and 72, containing the morpholine, naphthoquinone, quinoline and triazine cores (which have a recognized corrosion inhibitory activity) were synthesized, with yields ranging from 32% to 35%, characterized and evaluated for their anticorrosion activities in AISI 316 steel in simulated water medium containing 150,000 mg.L-1 of Cl- and 5 mg.L-1 of S2-. The potentiodynamic polarization study revealed that the three compounds synthesized showed corrosion inhibiting activity, with inhibition efficiency ranging from 66% to 85%, being the best result obtained for compound 70. The study of electrochemical impedance corroborated with the study of polarization, pointing to compound 70 as the best inhibitor and further indicated that the compounds studied act by forming a protective film on the surface of the AISI 316 steel. A fourth molecular hybrid 98containing only the triazine and naphthoquinone cores was also synthesized, however its structural characterization still requires some more analysis.